Determinação da suscetibilidade à vancomicina e avaliação de atributos de virulência em amostras de Staphylococcus aureus isoladas de bacteremias - Barbosa, Maralisi Coutinho (2018)
Staphylococcus aureus is one of the main pathogens causing a range of nosocomial and community infections. Bacteremias are constant and presents high rates of mortality and morbidity in worldwide. Vancomycin (van) is the empirical therapy for treatment of Gram-positive cocci infections in hemodialytic patients. In 1997, S. aureus strains arised with reduced susceptibility to van (VISA and hVISA). These isolates are associated with therapeutic failures by van and recurrence. The objective of this work was to characterize samples of S. aureus grown at high concentrations of van as for susceptibility and virulence attributes. Forty-one S. aureus strains isolated from hemodialytic patients with bacteremias (parental) were grown in 4 to 16 μg / mL of van and reisolated after this test, being called derivatives. Derivatives from all 41 S. aureus strains were isolated. All parental and derivatives strains were susceptible to van. The minimum inhibitory concentration (MIC) of van in the derivatives strains presented an increase in relation to the parental, but within the parameters established by the Clinical & Laboratory Standards Institute (CLSI). Twenty-four pulsotypes were identified using the PFGE technique and nine strains (22%) showed resistance to methicillin through the cefoxitin disc and amplification of the mecA gene. Nine derivatives strains isolated in 16 μg / mL van were able to grow in the presence of 8 μg / mL van. Biofilm and five hydrolytic enzymes production were smaller in the derivatives strains. The virulence of the derivatives strains was evaluated in an in vivo model with Galleria mellonella, with two derivatives strains showing decreased virulence and one increased. There was no difference between parentals and derivatives regarding autolysis, δ-hemolysin production, fibrinogen binding and metabolic viability. Although they grew at high van concentrations, the derivatives strains showed slow growth and MIC at the van susceptibility range, indicating tolerance. Of all the virulence factors tested, the selective pressure with van only affected the biofilm production and five hydrolytic enzymes. In the in vivo model the virulence of the derivatives was varied, indicating that it was straindependent.